739. Middle East Respiratory Syndrome Coronavirus Infection Profile in Qatar: A 7-Year Retrospective Study. (26th November 2018) - Elmaki, Nada; Abid, Fatma Ben; Farag, Elmubasher; Alsoub, Hussam; Ghazouani, Hafedh Ghazouani; Saleh, Mulham Mohed; Dousa, Khalid M; Al-Khal, Abdullatif; Hashim, Samar Mahmoud A; Al- Maslamani, Muna
Abstract: Background: A deadly zoonotic Middle East respiratory syndrome coronavirus ( MERS-CoV ) had emerged over the last 7 years in the Arabian Peninsula. As of February 28, 2018, 2, 182 cases of MERS-CoV infection (with 779 deaths) in 27 countries were reported to WHO worldwide. The objectives of this study were to identify the clinical and epidemiological characteristics of MERS-CoV infection as well as determine its clinical outcome. Methods: This was a retrospective-observational study of all laboratory confirmed cases of MERS-CoV infection conducted at the main seven hospitals in the State of Qatar from January, 2012 to April 2018. We used the Fast Track diagnostics real-time reverse-transcription polymerase chain reaction (rRT-PCR), targeting the upE and ORF1a genes respectively. Demographics, clinical information, potential contacts and probable risk factors were collected and analyzed by standard statistical methods. Results: The mean annual incidence was 1.7 per 100, 0000 person-years. Among the 24 confirmed cases of of MERS-CoV, males constituted the vast majority of cases (23 males) with a median age of 52 years (range 22–74). Fifty percent of the cases were Qatari and 42% reside in the same region. 67% of the cases had contact with camels, and 21% had contact with MERS-CoV -infected patient. Thirty-eight had travel history within 2 weeks of symptoms onset to the Kingdom of Saudi Arabia. Fifty percent were smokers and 42% had comorbidities. The median symptoms duration was 4.5 days. Most of the patient presented with flu-like symptoms, were fever was the most common presentation, followed by cough, SOB, diarrhea, abdominal pain and headache, 96%, 83%, 33%, 8%, 8% and 4%, respectively. All patients were admitted to a tertiary hospital with a median hospital stay 41 days (8–97). Forty-five percent patients developed severe sepsis with multi-organ failure and needed ICU admission. Fifty percent patients developed acute kidney injury, 29% patients were on hemodialysis and 16% needed extra-corporeal membrane oxygenation. Thirty-three percent patients died. The rest of patients had recovered from the infection and discharged home. Among those who died all had one or more comorbidities. Conclusion: MERS-CoV infection is a rare infection in the State of Qatar, seen in both Qataris and expatriates with and without travel history. The infection in patients with comorbidities carries high mortality. Disclosures: All authors: No reported disclosures.